Istvan Meszaros as communication theorist: the media in times of capital crisis - Rodrigues De Souza, Rafael Bellan [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2016)
The text presents the thinking of Marxist Istvan Meszaros, demonstrating its vitality to the field of communication. Based on the dialectical method places the debate around the social reproduction system in which we live as a universal shaft understanding of the communication. The Hungarian philosopher ontological matrix is presented as an alternative to the field of communication, putting on the agenda the return to historical materialism. In this article also we debates the structural crisis of capital, ideology as practical consciousness and the two mediations orders that constitute the social mode of production that may be related to the role of the media in the structuring of human sociability..
Keywords: communication; capital; Meszaros; marxism